Building towards community-oriented policing: Forming an academic medical center partnership with local police - Jessica Olson; Janine Tucker; Robert Simi; Shane Wrucke; C. Greer Jordan (Preventive Medicine Reports, 2022)
In the Spring of 2020, protective services for the Milwaukee Regional Medical Center (MRMC) Campus began a year-long transition process from the Milwaukee County Sheriff’s Department to the Wauwatosa Police Department (WPD). This transition occurred during a time of focused local and national discourse regarding policing in diverse community settings. In response, the MRMC leadership formed the Ad Hoc Advisory Committee for the Transition of Protective Services (AATOPS). Over the course of six months, AATOPS members conducted site visits, developed a training manual, and divided into subcommittees to establish recommendations and key performance indicators in four primary areas: 1) Diversity and Inclusion of the WPD; 2) Psychological Evaluation of WPD Officers; 3) Use and De-Escalation of Force within the WPD; and 4) Communicating the Imminent Transition of Protective Services to MRMC organization employees, faculty, students, trainees, and patients. In this paper, we detail the process of organizing an accountable and collaborative approach to police and medical and academic campus relationships. At the end of the transition period, both the WPD and MRMC expressed commitment to a continued partnership to ensure the safety and security of all on the MRMC campus.